Business mathematics - Lau, Too Kya; Phang, Yook Ngor; Wee, Kok Kiang (Oxford Fajar, 2019)
This books is especially written to cater to the needs of first and second year students in intitutes of higher learning who are pursuing diploma and degree courses in business studies, banking, investment analysis, public administration, tourism management, culinary art, office management and business administration.